The potential roles of gut microbiome in porto-sinusoidal vascular disease: an under-researched crossroad - Li, Yangjie; Lyu, Lingna; Ding, Huiguo (Frontiers in Microbiology, 2025)
Accumulating evidence indicates that patients with liver diseases exhibit distinct microbiological profiles, which can be attributed to the bidirectional relationship of the gut-liver axis. Porto-sinusoidal vascular disease (PSVD) has recently been introduced to describe a group of vascular diseases of the liver, involving the portal venules and sinusoids. Although the pathophysiology of PSVD is not yet fully understood, several predisposing conditions, including immunodeficiency, inflammatory bowel disease, abdominal bacterial infections are associated with the increasing in intestinal permeability and microbial translocation, supporting the role of altered gut microbiota and gut-derived endotoxins in PSVD etiopathogenesis. Recent studies have proposed that the gut microbiome may play a crucial role in the pathophysiology of intrahepatic vascular lesions, potentially influencing the onset and progression of PSVD in this context. This review aims to summarize the current understanding of the gut microbiome's potential role in the pathogenesis of hepatic microvascular abnormalities and thrombosis, and to briefly describe their interactions with PSVD. The insights into gut microbiota and their potential influence on the onset and progression of PSVD may pave the way for new diagnostic, prognostic, and therapeutic strategies.